La Famille Dansant. Investigating the Family Structure and Repertory of the Johannesénske Balletselskab - Fiskvik, Anne Margrete (Nordic Theatre Studies, 2015)
The performance history of the Johannesénske Balletselskab spans a long period. In different shapes, sizes and names the ensemble was on the road for 30 years. This article analyses the activities of the Johannesénske enterprise through the lenses of itinerant performance traditions. Two features are discussed in this article: the reliance on family members as performers and the ensemble’s diverse repertory. The ensemble featured a repertory popular in its own time, consisting chiefly of national and character dances as well as pantomimes. Arguably, an investigation of the ensemble’s performance history offers information on little explored perspectives of nineteenth century Nordic ballet. In particular, the Johannesénske Balletselskab offers insights into family structures and the repertoire typical of itinerant ensembles. This information is also useful on a more general level, given that there were several ensembles similar to the Johannesénske travelling in the Nordic countries that functioned similarly to La famille dansant. Through analysing the use of the repertoire, it can be shown that the Johannesénske enterprise was, in their programming, up to date as a “ballet ensemble”. The family kept up itinerant traditions through their use of children as performers and reliance on pantomimes. The Johannesénske ensemble is, therefore, especially valuable for revealing insights into dance practices and dance styles, which have, so far, been little researched.